ANALISA KEPUASAN MASYARAKAT TERHADAP KINERJA PELAYANAN KANTOR CAMAT KECAMATAN SAROLANGUN - - Dahmiri (Kompetensi (Competence : Journal of Management Studies), 2014)
This Research showing there are 3 (three) dimensions in good categories which are; the service procedure,the ability of service workers,and tehe environment safety. There are two ungoods dimensions; the fairness to get service, and the fairness to knowing how the service’s cost. There are nine dimensions are being in less condition  those are ; term of service, clarity of the service workers, the disciplinary of service workers,the responsibility of service workers, the speed of service, the hospitality of service, and the fairness of the service cost,certainty of service schedule and the comfortable of the environmental.